APLIKASI MATRIKS HANKEL PADA PERHITUNGAN RESULTAN DUA POLINOMIAL - Rosnawati, R (Faculty of Mathematics and Science Education, Universitas Pendidikan Indonesia, 2002)
Let F be a field,Â f and g in F[x], with degre f is n and degre g is m. Computing resultant two polynomialsÂ with Hankel matrics give a size of matrics less than Sylvester method, that is maximum n or m.